Bahasa Non Baku Dalam Media Sosial: Dampak Terhadap Pemahaman Dan Komunikasi - Irmawaty Tambunan; Naia Rencani Suci; Enggis Br Siagian; Elfretty Br Sitanggang; Yuni Melati Simare-mare; Onyx Nifty; Malan Lubis (Universitas Maritim AMNI Semarang, 2024)
This study examines the impact of standardized language use in social media on users' understanding and communication. With the increasing dominance of social media as a communication platform, the use of appropriate language is important to ensure messages are well received and understood. This study used survey method to collect data from various age groups and educational backgrounds. The results show that the use of standardized language tends to increase clarity and politeness in communication, but can also cause difficulties for users who are less familiar with formal language rules. This study concludes that although standardized language has an important role in improving comprehension, adaptation and flexibility in its use need to be considered in order to maintain effective communication on social media.